SSATP Review of National Transport and Poverty Reduction Strategies : Guidelines - Braithwaite, Mary (World Bank, Washington, DC, 2014)
This report discusses the process and methodology involved in developing a practicable method for undertaking a comparative analysis of transport sector and poverty reduction strategies. The report notes that this is an important milestone in a process that has been ongoing since the 2000 Business Meeting and Initial General Assembly of SSATP. Those meetings began the SSATP Strategic Review and formulation of new governance arrangements. The outputs of the Strategic Review resulted in demands being expressed by country coordinators for the transport sector to better demonstrate its contribution to poverty reduction and for a move towards a more integrated, programmatic approach within SSATP. The strategic goal of the program is to ensure that transport sector strategies are firmly anchored in overarching poverty reduction strategies was established at the 2002 SSATP Stakeholders' Meeting in Maputo, Mozambique. The guidelines are designed with a participatory methodology for the comparative assessment, which was tested out by three countries: Guinea, Rwanda and Tanzania during the first half of 2003. These guidelines are the result of the experimentation and verification by transport and poverty reduction strategy personnel in sub-Saharan Africa.